Image retrieval based in wavelet features - Lim, Shih Hsien. (2008)
Increasingly vast amounts of visual media, such as photographs and videos, are stored in digital form. The Internet is an example where terabytes of digital visual information can be viewed on-line. There is thus a great need to develop systems for managing, indexing and searching visual information.